2017
DOI: 10.15405/epsbs.2017.05.02.110
|View full text |Cite
|
Sign up to set email alerts
|

Students' Perception Concerning the Career Counselling Programs

Abstract: Students' perception concerning the career counselling programs is determined by the extent to which these programs are adjusted to their counselling needs. The present study is based on a constatative and correlational design and is conducted on a population of 257 students (N=257). These participants were aged between 19 and 21 years. 77 were males and 180 females.The research aims to investigate how the career counselling activities, conducted during the SOPHRD program SOPHRD/161/2.1/G/137510 entitled Profe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Research has shown that the use of these tests has reduced by almost half (42%) the distraction of students and the considerable increase in grades obtained by them. (Szpunar et al, 2013) Teachers have gradually begun to approach online education differently (Crișan et al, 2017;Oltean, 2016;). From the amphitheatres, from the blackboard, from the chair, from the bench, teachers and students were forced at the beginning of 2020 to find themselves exclusively in front of the screens.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that the use of these tests has reduced by almost half (42%) the distraction of students and the considerable increase in grades obtained by them. (Szpunar et al, 2013) Teachers have gradually begun to approach online education differently (Crișan et al, 2017;Oltean, 2016;). From the amphitheatres, from the blackboard, from the chair, from the bench, teachers and students were forced at the beginning of 2020 to find themselves exclusively in front of the screens.…”
Section: Introductionmentioning
confidence: 99%